Eyes of the RAF a history of photo-reconnaissance - Nesbit, Roy Conyers (Sutton Publishing, 2003)
RAF air photography has come a long way from faltering beginnings over the trenches of the Western Front during the First World War, when unwieldy plate cameras were fixed on the cockpit sides of Royal Aircraft Factory BE2 biplanes. By the close of the Second World War dedicated photo-reconnaissance Spitfires could photograph the enemy by day, while Mosquitos could operate by day or night from heights up to 36,000 feet. With the quantum leap in recent decades of electronics and optical imagery, Panavia Tornado GRs can use video-tape with a data link to relay pictures to image analysts on the ground, thus doing away with 'wet' film techniques. Eyes of the RAF was written at the request of the Association of Royal Air Force Photography Officers and is the only book currently available on this fascinating subject. Using official and personal records, the author traces the development of air photography from the earliest days to the present era. His detailed narrative is supported by more than 400 photographs with exhaustively researched captions, making it the most comprehensive history yet written on the RAF's photo-reconnaissance capability.